Genetic diversity in the Diplosoma listerianum complex (Ascidiacea: Didemnidae) from the Western Atlantic. Issue 8 (17th November 2021) - Rocha, Rosana M.; Teixeira, Joyce Ana; Barros, Rodolfo Corrêa de
Abstract : (Received 19 January 2021; revised 27 September 2021; accepted 27 September 2021) Diplosoma listerianum has been re-described with more than 40 currently invalid names, but recent data suggests that some of those names may be valid. At least four distinct clades were recently revealed by molecular analysis using mitochondrial DNA (mtDNA). Yet, very few samples were analyzed from the western Atlantic, of which none were from the extensive Brazilian coast. Here, we analyze genetic diversity in D. listerianum in light of morphological data. We sequenced 55 samples from Brazil, Panama, Mexico, and the United States and analyzed them together with published data, to test whether local populations are part of widespread, known, clades or are native species hidden within this complex. Phylogenetic analysis found eight clades, three of which were different from the ones recovered before. Former clade A was split into two larger clades: clade A1 occurs in the western Atlantic, on the Pacific side of Panama and in South Africa; clade A2 occurs worldwide, with representatives found on every continent. Species delimitation analyses (ABGD, bPTP and GMYC) found 16 MOTUs, which suggests that those large clades are very diverse and may comprise more than one species. Diversity was greatest in Panama (6 clades) and Mexico (3 clades). Larval morphological characters were examined and described here. However, for only a few of the sequenced samples could fully grown larvae be obtained and phenotypic variation was large. Thus, larval morphology could not be used to diagnose molecular clades. Diplosoma listerianum remains a species complex, with evidence of ongoing speciation, and high genetic diversity, especially in the tropical western Atlantic. Fast-growing colonies, rapid life cycles, and amenability to cultivation in the laboratory indicate that this species can be a model for studies in speciation.